Knowledge-Based and Intelligent Information and Engineering Systems 13th International Conference, KES 2009, Santiago, Chile, September 28-30, 2009, Proceedings, Part I - Velásquez, Juan D.; Ríos, Sebastián A. (Lecture Notes in Artificial Intelligence, 2009)
The two-volume set LNAI 5711 and LNAI 5712 constitutes the refereed proceedings of the 13th International Conference on Knowledge-Based Intelligent Information and Engineering Sysetms, KES 2009, held in Santiago de Chile in September 2009. The 153 revised papers presented were carefully reviewed and selected from numerous submissions. The topics covered are: fuzzy and neuro-fuzzy systems, agent systems, knowledge based and expert systems, miscelleanous generic intelligent systems topics, intelligent vision and image processing, knowledge management, ontologies and data mining, web intelligence, text and multimedia mining and retrieval, other advanced knowledge-based systems, innovations in chance discovery, advanced knowledge-based systems, multi-agent negotiation and coordination, innovations in intelligent systems, intelligent technology approach to management engineering, data mining and service science for innovation, knowledge-based systems for e-business, video surveillance, social networks, advanced engineering design techniques for adaptive systems, knowledge technology in learning support, advanced information system for supporting personal activity, design of intelligent society, knowledge-based interface systems, knowledge-based multi-criteria decision support, soft computing techniques and their applications, immunity-based systems. The book also includes three keynote speaker plenary presentations.